Production, characterization and evaluation of the chemotherapeutic and immunogenic potential of protein based virus-like particles in tumoral and immune cell lines - Gonçalves, Amanda Patrícia (2023)
In this thesis, nanotechnology was used to develop three inedited platforms with clinical applications. Results are presented in three chapters written in article format. In the first chapter, in vitro assays are used to characterize a new doxorubicin (DOX) carrier virus-like platform and to evaluate the cell effects of murine melanoma cells treated with free DOX or carried DOX. It is showed that carried DOX promotes higher cell death rates and enter cells in a different manner whether compared with free DOX. In the second chapter, the Spy Catcher/Spy Tag technology was used to conjugate different peptides to rod-shaped virus-like particles (VLPs). It is shown that two different types of antigen-presenting cells (APCs) can take up decorated VLPs and this promotes the activation of immune response by increasing CD80 and CD86 expression. In the third chapter, Spy Catcher/Spy Tag technology was also used to conjugate anti-EGFR nanobodies to the surface of DOX-loaded VLPs. It is shown that particles displaying anti-EGFR nanobodies promote a more accentuated decrease on cell viability of human colorectal cancer cells whether compared with non-decorated particles. In conclusion, this work present the full production and characterization of three distinct nanoplatforms and a solid in vitro evaluation of a range of cell mechanisms such as endocytosis, apoptosis and autophagy. The achieved results suggest that the constructions presented here have features that put them as nanoplatforms with potential clinical applications such as vaccine platforms and drug delivery systems. Keywords: Nanotechnology. Drug-delivery systems. Vaccine platforms. Protein-based particles. Nucleic acid-based particles. Particle decoration. Doxorubicin. Cancer.